Synthesis and reactions of new pyrimidines containing functionalised side chains - Duff, Thomás D. (Trinity College (Dublin, Ireland). School of Chemistry, 2000)
Thin layer chromatography was carried out using Merck Kiesgel 60 F254 0.2 mm silica gel plates. Visualisation was by means of ultra violet light at 254 nm or by development in potassium permanganate solution. Flash chromatography was carried out using Merck Kieselgel 60 (mesh 230-400 ASTM) silica gel. 'Concentration' of solutions refers to the use of a Buchi rotary evaporator. Dry THF was obtained by first drying over potassium hydroxide pellets for 24 hours, then distilling from lithium aluminium hydride and finally distilling from sodium benzophenone ketyl.
Keywords: Chemistry, Ph.D.; Ph.D. Trinity College Dublin